Transformation of Healthy Islamic Boarding Schools: Dengue Education and Larva Monitoring Website for Students Through Digital Engagement - Sri Astutik Andayani; M. Syafii; Setiyo Adi Nugroho; Rinda Riyani Julifianti; Robiatul Adawiyah (GUYUB: Journal of Community Engagement, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health challenge in Indonesia, particularly in densely populated environments such as Islamic boarding schools (pesantren). Crowded dormitories, shared sanitation facilities, and numerous water containers create favorable conditions for mosquito breeding, resulting in recurrent dengue cases and low larva-free indices in several pesantren in East Java. This community-based program was implemented to strengthen dengue prevention through the integration of structured health education, simple ovitrap technology, and a digital larva-monitoring website as a digital engagement model for Santri Jumantik. The program employed a pre-experimental one-group pretest–posttest design conducted over three months (September–November 2025) at a pesantren in Probolinggo, involving 30 students. Interventions included dengue and PHBS education, hands-on training in constructing low-cost ovitraps from recycled materials, and weekly larval surveillance reported through a web-based monitoring system. Data were collected using knowledge questionnaires, ovitrap observations, larva-free index (ABJ) measurements, and website activity logs, and analyzed descriptively and using the Wilcoxon Signed Rank Test.The results demonstrated a significant improvement in students’ knowledge (Z = –3.996; p < 0.001), with high-level knowledge increasing from 26.7% to 86.7%. Ecological indicators also improved, as the ABJ increased from 72% to 80% and ovitrap positivity declined over time. Digital reporting compliance reached 92%, indicating strong student engagement. This integrated approach effectively strengthened dengue prevention practices and offers a scalable model for transforming pesantren into healthier learning environments.